Dietary anthocyanins: A review of the exercise performance effects and related physiological responses - Cook, M. D.; Willems, M. E. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Foods and supplements high in anthocyanins are gaining popularity within sports nutrition. Anthocyanins are pigments within berries and other colorful fruits and vegetables. They have antioxidative and anti-inflammatory actions that improve recovery from exercise. Furthermore, anthocyanins can also affect vasoactive properties, including decreasing mean arterial blood pressure and increasing vasodilation during exercise. In vitro observations have shown anthocyanin- and metabolite-induced activation of endothelial nitric oxide synthase and human vascular cell migration. However, effects of anthocyanins on exercise performance without a prior muscle-damaging or metabolically demanding bout of exercise are less clear. For example, exercise performance effects have been observed for blackcurrant but are less apparent for cherry, therefore indicating that the benefits could be due to the specific source-dependent anthocyanins. The mechanisms by which anthocyanin intake can enhance exercise performance may include effects on blood flow, metabolic pathways, and peripheral muscle fatigue, or a combination of all three. This narrative review focuses on the experimental evidence for anthocyanins to improve exercise performance in humans.